Penjemur Kerupuk Otomatis Menggunakan Sistem Kecerdasan Buatan Arduino Uno Dengan Menerapkan Metode Fuzzy Logic Controller (FLC) - Risal Suandi (STMIK Budi Darma, 2020)
Denang jangek cracker factory is a company located on the road denai Kota medan, this factory everyday produces jangek crackers, at the stage of production there is a stage of drying jangek crackers used manually, where crackers are placed outside the room exposed to the sun's heat at the drying stage . When the rainy season arrives this makes a lot of time taken up during the drying process because often it rains suddenly, then the crackers must be immediately put in or placed in a dry place not exposed to rain water. The FLC method is a method that is often used in making artificial intelligence systems that are applied to an Arduino uno microcontroller where the method only recognizes on or Off, 0 or 1, nothing is vague. From the description of the problem above, the writer makes an artificial intelligence system that is applied to a device, namely Arduino Uno, where the system thinks like humans, who can think like when it rains so that the tool will move or close crackers that are being dried in the sun so that it is not exposed to rain with using an FLC method applied to Arduino Uno